Developing a Mentorship Program in Higher Education Institutions - Jonathan M. Orsini; Matthew P. Benge; Hannah S. Carter (EDIS)
Higher education institutions are currently tackling a growing number of organizational challenges that have forced departments to evolve their business practices. Administrators are faced with the need for more diverse programs which require facilities, faculty, and services, and must decide whether to develop talent internally or recruit new qualified candidates (Kutchner & Kleschick, 2016). Given the great cost of faculty searches, and the perceived diminishing availability of talented applicants, it is imperative that administrators understand the importance and value of mentoring relationships to fill needs with qualified candidates in higher education institutions. However, formal mentoring programs have been slow to develop in higher education institutions. This publication defines mentorship, explains the value of mentorship, and describes how mentoring programs can be established.